The effects of instructional methodology and learning style on problem solving in baccalaureate nursing students enrolled in an introductory pharmacology course. - Hill KYB (Effects of Instructional Methodology & Learning Style on Problem Solving in Baccalaureate Nursing Students Enrolled in an Introductory Pharmacology Course, 1998)
The primary purpose of this quantitative study was threefold: (1) to compare the effectiveness of two instructional methods of teaching on transferring problem solving; (2) to identify the effect a student's learning style has on problem solving; and (3) determine whether an interaction exists between each of two instructional methods and the student's learning style that effects the problem solving ability of beginning nursing students enrolled in a nursing pharmacology course in a four-year baccalaureate (B.S.N.) nursing program. The content area was pharmacology for nurses, taught at the sophomore level in a 4-year program. A convenience sample consisted of 48 adult nursing students in two different sections of a required pharmacology course in one B.S.N. program. The teaching methods studied were lecture/discussion and experiential/active methodology. The sample consisted of two groups, one taught by lecture-discussion (n = 25) and the other taught by the experiential method (n = 23). A pretest, posttest design using a faculty made 30-item objective test in pharmacology content was used to measure problem solving ability. The learning style of the students in both groups was assessed using the Learning Styles Inventory (LSI) developed by David Kolb. The theoretical foundation for the study was drawn from the work of Jerome Bruner, Jean Piaget, Shirley Schriver, and John Clark.Non-parametric statistics were used to test for statistically significant differences in the two groups in the study. A two-way analysis of covariance (ANCOVA) was used to investigate the effect of teaching methods, learning styles, and an interaction of method and learning style on problem solving.